Assessing Drug-Induced Long QT and Proarrhythmic Risk Using Human Stem-Cell-Derived Cardiomyocytes in a Ca2+ Imaging Assay: Evaluation of 28 CiPA Compounds at Three Test Sites. (24th April 2019) - Lu, Hua Rong; Zeng, Haoyu; Kettenhofen, Ralf; Guo, Liang; Kopljar, Ivan; van Ammel, Karel; Tekle, Fetene; Teisman, Ard; Zhai, Jin; Clouse, Holly; Pierson, Jennifer; Furniss, Michael; et al.
Abstract: The goal of this research consortium including Janssen, MSD, Ncardia, FNCR/LBR, and Health and Environmental Sciences Institute (HESI) was to evaluate the utility of an additional in vitro assay technology to detect potential drug-induced long QT and torsade de pointes (TdP) risk by monitoring cytosolic free Ca 2+ transients in human stem - cell-derived cardiomyocytes (hSC-CMs). The potential proarrhythmic risks of the 28 comprehensive in vitro proarrhythmia assay (CiPA) drugs linked to low, intermediate, and high clinical TdP risk were evaluated in a blinded manner using Ca 2+ -sensitive fluorescent dye assay recorded from a kinetic plate reader system (Hamamatsu FDSS/µCell and FDSS7000) in 2D cultures of 2 commercially available hSC-CM lines (Cor.4U and CDI iCell Cardiomyocytes) at 3 different test sites. The Ca 2+ transient assay, performed at the 3 sites using the 2 different hSC-CMs lines, correctly detected potential drug-induced QT prolongation among the 28 CiPA drugs and detected cellular arrhythmias-like/early afterdepolarization in 7 of 8 high TdP-risk drugs (87.5%), 6 of 11 intermediate TdP- risk drugs (54.5%), and 0 of 9 low/no TdP- risk drugs (0%). The results were comparable among the 3 sites and from 2 hSC-CM cell lines. The Ca 2+ transient assay can serve as a user-friendly and higher throughput alternative to complement the microelectrode array and voltage-sensing optical action potential recording assays used in the HESI-CiPA study for in vitro assessment of drug-induced long QT and TdP risk.